Pseudomyxoma peritonei, Appendiceal neoplasms, survival benefits from Cytoreductive Surgery & Hyperthermic Intraperitoneal Chemotherapy A 15 years analysis - Spiliotis, John; Iavazzo C; Rogdakis A; Stefanopoulou P; Spiliotis NJ; Koupanis C; Raptis A; Noskova I; Karachalios D; Christopoulou A (Journal of Medical Biomedical and Applied Sciences, 2022)
Abstract BACKGROUND: This study explores the impact of cytoreductive Surgery and Hypertermic Intra PEritoneal Chemotherapy (HIPEC) on pseudomyxoma peritonei (PMP), appendiceal neoplasms through a safety analysis completed by evaluation of survival performances. METHODS: Retrospective chart review of 111 patients were diagnosed with appendiceal neoplasms during the period November 2005 to November 2019. Safety was evaluated by means of procedural morbidity and mortality. Survival performances included disease-free survival (DFS), and overall survival (OS) as end points. RESULTS: The median age of the patients was 52,5 years (range 28-72 years). Among them, 62 were female (55,8%) and 49 male (44,2%). The median time interval between the initial diagnosis and the definitive treatment with CRS + HIPEC was 9 months (range 4-20 months). The majority of our cases were high grade mucinous adenocarcinomas (39,6%). Postoperative complications, type 3 and 4 according to the Clavie-Dindo classification were identified in 10/111(9,2%) and postoperative deaths were observed in 4/111(3,6%). The cohort median overall survival (OS) for all patients was 57,1 months (95% CI, 42,8-71,6m). Better OS was observed in mucinous only PSM which was estimated up to 142,8 months (CI 95% 98,8-186,5 months) and worse in high grade signet-ring mucinous adenocarcinoma which was estimated down to 23,6 months (CI 95% 20,2-27,1 months). Mean DFS was 36,44m (95% CI, 24,05-48,83m). CONCLUSION: PMP is a rare disease that presents with a wide range of histological types and disease behavior. When patients present with diffused abdominal disease and peritoneal spread, CRS plus HIPEC is an accepted treatment which showed that could improve survival in carefully selected patients treated by subspecialists in tertiary referral centers. Keywords: Pseudomyxoma peritonei, Appendiceal neoplasms, survival, HIPEC